Global Landscapes Forum - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
On 16-17 November, the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) and the Center for International Forestry (CIFOR) came together to put together a Global Landscapes Forum (GLF) in the midst of the ongoing Climate Talks in Warsaw, Poland, also known as COP19. The meeting featured several high-level speakers and plenty of discussions and networking.